Sistema de seguridad telemático aplicado al sector industrial para la autenticación de reconocimiento de IMAGEN - Tamami González, Glenda Alexandra (2024)
In response to the growing importance of industrial security, this research focuses on implementing an innovative system based on image recognition techniques to authenticate operators in industrial environments. The objective is to ensure safe access to restricted areas, prevent accidents and safeguard assets. Exploratory, analytical, and field methods are applied to obtain detailed and accurate information about study. Image recognition approaches and algorithms will be explored, addressing challenges such as lighting variability and adverse conditions. The proposal seeks to improve occupational safety worldwide, considering international regulations and alarming occupational accident statistics. It highlights the efficiency of the system, its compliance with ISO standards, the reduction of unsafe behaviors, and the improvement of productivity. In addition, a current diagnosis and a prognosis suggesting process automation and resource optimization are presented. The problem formulation focuses on the effective implementation of the telematics system, with clear independent and dependent variables. Key questions are raised about the choice of recognition techniques, system evaluation and regulatory compliance. The purpose of the study is to develop an improved system that offers greater safety, efficiency, and accuracy. This includes investigating traditional methods, designing the telematics system to comply with regulations, and evaluating its performance. This project seeks to pioneer the implementation of advanced industrial security solutions, setting the standard for future developments in the field